Relationship Between Money Laundering Crime and Corruption Crime as Originate Crime From the Criminal Perspective - Nani Widya Sari; Henny Nuraeny; Oksidelfa Yanto; Guntarto Widodo; Bhanus Prakash Nunna (International Journal of Integrative Sciences, 2023)
The purpose of this research is to understand and analyze an act that can be categorized as a money laundering crime complete with all its elements. Then also understand and analyze the relationship between money laundering crimes and corruption crimes. The research method used is the normative legal research method through literature study with the data source, namely secondary data. The research results show that the crime of money laundering cannot be separated from the original act, namely the crime of corruption. In processing a money laundering crime, it is not necessary to prove the predicate crime first, because the object of the money laundering crime is the assets resulting from the predicate crime